2023
DOI: 10.1108/agjsr-10-2022-0223
|View full text |Cite
|
Sign up to set email alerts
|

The association between fingerprint patterns and blood groups in the Omani population

Abstract: PurposeFingerprints and blood samples are important for the identification of individuals and criminals. The present study aims to identify the predominant fingerprint patterns and the association between the fingerprint patterns and ABO–Rh blood groups in Omani population.Design/methodology/approachA cross-sectional study was conducted on 200 Omani individuals aged 18 years (104 males and 96 females). The imprints of all right and left-hand fingers were taken, and the types of the fingerprints were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…The results of a study conducted on Omani population suggested that the predominant fingerprint pattern among their study population was loop (49.4%), followed by whorl (44.9%) and then arch (5.7%) pattern. 14 Similar results were documented by majority of other studies from different parts of the world. The loop was the most common pattern observed in a study by Patil et.…”
Section: Discussionsupporting
confidence: 88%
“…The results of a study conducted on Omani population suggested that the predominant fingerprint pattern among their study population was loop (49.4%), followed by whorl (44.9%) and then arch (5.7%) pattern. 14 Similar results were documented by majority of other studies from different parts of the world. The loop was the most common pattern observed in a study by Patil et.…”
Section: Discussionsupporting
confidence: 88%
“…Tarik Al Habsi along with his team studied the association between fingerprints and blood groups in the Omani population and found that loop fingerprint pattern was the most common in Omani subjects (49.4%), followed by whorl (44.9%) and arch (5.7%) pattern, loop occurring more in females than in males and the test also revealed a significant correlation between different fingerprint patterns and blood groups of the subjects but never mentioned about their inheritances relationship (10) .…”
Section: Review Of Literaturementioning
confidence: 99%
“…Одним из ключевых направлений повышения продуктивности аграрного сектора являются новые подходы в мелиорации, они позволяют повысить урожайность и качество сельскохозяйственной продукции. Сегодня в этой сфере наблюдается ряд тенденций, связанных с цифровизацией, искусственным интеллектом, новыми технологиями и эффективным управлением (Загоровская, 2020;Куприяновский, 2016;Шпорер, 2022;Юрченко, 2021;Al Habsi, 2017…”
unclassified